Musical Expression On The Ksyr Lestari Group’s The Sintren Art Of Luwijawa Village In Tegal Regency (Jurnal Seni Musik, 2022)
The KSYR Lestari Sintren art group is an art group that has musical expressions in their performances with songs that are played and add various atmospheres to the performance of each scene. The songs of the Sintren art show involve the musical function of Sintren art dance performed by the KSYR Lestari group. This study aims to identify and explain the musical expression of the song type performed and the musical function of the Sintren art dance of the KSYR Lestari group. This study used a qualitative research method with a phenomenological approach and the data collection techniques used in this study are observation, interview, and documentation. The results of this study indicate that the musical expressions contained in the KSYR Lestari Sintren art through songs performed include; (1) Tempo, the song Dunung Ala Dunung is played at a slow tempo which expresses feelings of sadness, and the song Turun Sintren is played at a fast tempo which describes a happy expression. (2) Dynamic, in every song that is sung, there are dynamic changes (3) The style produces tones on four vocalists who have been selected according to the character of the voice and song. Sintren performance elements include; (1) Theme, (2) Dancer, (3) Fashion, (4) Makeup, (5) Movement, (6) Accompaniment, (7) Stage arrangement, (8) Lighting and sound system, (9) Property. The function of music in Sintren dance includes; (1) Music as a dance binder, and (2) Music as a dance illustration.